Obława Augustowska – stan badań, ich uwarunkowania i perspektywy - Jasiewicz, Krzysztof (Studia z Dziejów Rosji i Europy Środkowo-Wschodniej, 2019)
Tekst stanowi autorską próbę oceny wiedzy historycznej na temat Obławy Augustowskiej, a także polemikę z ustaleniami innych historyków oraz działaniami Białostockiego Oddziału IPN. The Augustów Roundup – current state of research, its circumstances and perspectives In January 1944 the Soviet Army crossed the former eastern border of the Second Polish Republic. With the help of the army, military formations of NKVD and military counter-intelligence SMERSH, a large-scale cleansing of the held territories started. The Augustów Roundup was the last of the large „counter-intelligence actions” of the battalion of the SMERSH Directorate troops of the 3rd Belorussian Front. It had all the hallmarks of the Katyń operation. A group, probably counting several hundred Chekists, was responsible for the physical elimination of the identified detainees. It seems that the Soviets must have had their own method of filtration in addition to a prior intelligence work. It might have been the 5-day cycle of interrogation. The detainees were beaten into the confession of being AK members or into indicating people suspected of it. A completely different technique of detention of the arrested can be observed. They were kept in small groups – a few–several persons without the right to correspondence. They were killed in the middle of nowhere, but probably, just like in the Katyń-mode, a building of some kind was necessary. The people might have been killed naked or were disrobed post-mortem to rule out identification in case the gravesite was found. Probably the remains of the victims of the Augustów Roundup are buried on the „Russian” side of the border. Now, when we are sure that the Roundup was also conducted in parts of Lithuania (not counting the investigations against the individuals placed at the disposal of NKVD-NKGB administration), as well as in a part of the Grodno region, the perfect place – from the logistic point of view – seems to be the intersection of the Polish, Lithuanian and Belorussian borders, somewhere in the vicinity of the village of Kalety, a rangers station of Giedź and the lake of Szlamy. The Augustów Roundup comprises several stages. The first one involved collecting information on Polish sovereignist underground by Soviet undercover agents and guerrillas. Perhaps, the May–June 1945 arrests might be included into this stage, starting with the arrests at the village fête in Studzienniczna in Augustów Forest. The second stage – between 12 and 19 July – was a military operation with the participation of the 62nd Division of the Interior Army of the NKVD, SMERSH officers and the local UB (secret security) and MO (militia). The third phase was a process of secondary detentions caused by the investigation by tortures to extract further information on the Polish underground. It took place between 20–21 July and autumn 1945. At this stage there were also executions. The fourth phase – from 1945/1946 to the Third Polish Republic – a protecting of the secret of the dissapearance and covering the tracks, probably with the help of the Russian secret service and Polish descendants of the people involved in the Augustów Roundup on the side of the perpetrators. Августовская облава – состояние исследований, определяющие их факторы и перспективы В январе 1944 г. Советская армия перешла восточную границу 2-й Польской Республики. С помощью армии, войск НКВД и военной контрразведки СМЕРШ началась крупномасштабная зачистка занятой территории. Августовская облава была последней из больших «контрразведывательных акций» армейского батальона Управления СМЕРШ-а 3-го Белорусского фронта. У нее были все признаки схожие с Катыньской операцией. Группа, предположительно, состоящая из нескольких сот чекистов занималась ликвидацией определенных задержанных. Кажется, у советов должны были быть свои методы во время фильтрации, кроме заранее проведенной разведывательной разработки. Может быть для этого употреблялся пятидневный цикл допросов. Задержанных избивали, чтобы те признались в членстве в Армии Крайовой или указали на лица, подозреваемое в этом. Отчетливо видна другая техника передержки арестованных. Они в очень небольших группах – в несколько человек, без права на переписку. Их убивают на пустошах, хотя, предположительно – так же как и в Катыньском «режиме» – нужно какое-то здание. Нельзя исключить, что людей убивали голыми или после смерти с них срывали одежду, чтобы, в случае находки могил, исключить какую-либо идентификацию. Вероятно, останки жертв Августовской облавы покоятся на «российской» стороне границы. Сейчас, когда у нас уверенность в том, что облава обхватывала часть Литвы, не считая дел возбужденных против людей, переданных в распоряжение органов НКВД-НКГБ, а также часть Гродненщины, идеальным местом, в логистическом отношении, кажется стык границ Польши, Литвы и Беларуси, где-то в окрестностях деревни Калеты, лесничества Гедзь и озера Шлямы. Августовская облава состояла из нескольких этапов. Первый заключался в собрании агентурой и собственным партизанским движением информации о польском подполье защитников независимости. Может быть к этому этапу можно причислить уже майские-июньские аресты, начиная с арестов во время народного гулянья в Студщенничной в Августовской пуще. Второй этап – между 12 и 19 июля – это военная операция, в которой принимали участье 62-я дивизия внутренних войск НКВД, работники СМЕРШ-а, местного УБ (служба безопасности) и МО (милиция). Третий этап – это процесс вторичных арестов, вызванных следствием с пристрастием, добывающем очередную информацию о польском подполье, который продолжался с 20–21 июля до осени 1945 г. На этот этап приходятся казни. Четвертый этап – с 1945/1946 по времена тн. 3-й Польской Республики – защита тайны исчезновения и сокрытие следов, может быть с помощью российских служб и польских потомков людей, замешанных в Августовскую облаву на стороне виновников.